Law no 149 of the year 2019 on Issuing the Law Regulating The Practice of Non-Governmental Work = قانون رقم 149 لسنة 2019 بإصدار قانون تنظيم ممارسة العمل الأهلي. (2025)
Law no. 149 of the year 2019 on Issuing the Law Regulating the Practice of Non-Governmental Work – part 1: definitions – part 2: associations – part 3: public benefit associations – part 4: non-governmental institutions – part 5: foreign non-governmental organizations – part 6: central unit of association and non-governmental work and the sub-units affiliated thereto – part 7: non-governmental associations and institutions projects support fund – part 8: the general federation, the regional and specific federations – part 9: volunteering – part 10: penalties قانون رقم 149 لسنة 2019 بإصدار قانون تنظيم ممارسة العمل الاهلى – الباب الأول التعريفات – الباب الثانى الجمعيات – الباب الثالث الجمعيات ذات النفع العام – الباب الرابع المؤسسات الأهلية – الباب الخامس المنظمات الأجنبية غير الحكومية – الباب السادس الوحدة المركزية للجمعيات والعمل الاهلى والوحدات الفرعية التابعة لها – الباب السابع صندوق دعم مشروعات الجمعيات والمؤسسات الاهلية – الباب الثامن الاتحاد العام والاتحادات الاقليمية والنوعية – الباب التاسع التطوع – الباب العاشر العقوبات